A água na educação ambiental: discussão sobre o ciclo hidrossocial a partir da pegada hídrica cinza da soja na região Sudoeste do Paraná - Gessi , Elisandra Aparecida Callegari (2023)
Environmental education constitutes an important formative and questioning process of the prevailing socio-environmental relations today. We consider that its performance is enhanced by the connection of local data to global environmental problems, which is why we problematize the use of water as a methodological resource for the development of educational processes on the hydrosocial cycle. We use bibliographical research as a methodology to describe examples of water uses in the southwest region, based on the hydrosocial cycle of a product, developing proposals for studies based on environmental education based on the collected data. We calculated and analyzed the gray water footprint – amount of water derived from the use of pesticides – resulting from soy production, based on SEAB data from the 2009/2010 and 2020/2021 soy harvests and the precipitation data provided for this same period by SIMEPAR for the 42 counties that compose the Southwest of Paraná. The calculations carried out result in the amount of 257,535,827 million m³ of gray water (2009/2010 harvest) and 308,915,510 million m³ of gray water (2020/2021 harvest). With direct products, an interactive map was created with the gray water footprint of soybeans in all municipalities in the Southwest of Paraná; the layout of the hydrosocial cycle of soybean oil production and the didactic presentation of the formula for calculating the gray water footprint of soybeans and the representation of the hydrosocial cycle of oil. We also discussed, based on the concepts of water footprint, gray water footprint and virtual water, about the amount of water used in this production process and the results of this indirect consumption. Based on data analysis, we created didactic-training material for teachers with proposals for issues and how they can be addressed in education, with the aim of enabling teachers and students to study relevant daily situations for the present and the future of water. We understand environmental education as a process of graduation, awareness, guidance and subsidy for a world with more equity in terms of the use and guarantee of the natural resource water.